High-strength and high-toughness R-T-B rare earth permanent magnet and preparation method thereof
By synergistically adding Ti and Nb elements to the R-T-B rare earth permanent magnet and performing high-temperature heat treatment on the Nb-containing SC sheet to form fine and dispersed precipitates, the problems of magnet brittleness and low second phase strengthening efficiency are solved, and the preparation of high-strength and high-toughness is achieved.
Patent Information
- Application Number
- CN202411802494.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-04-11
AI Technical Summary
Due to the properties of the brittle material, R-T-B rare earth permanent magnets are prone to brittle breakage, which limits their application environment. The existing second phase strengthening method has the problem of reduced stray fields and diffusion caused by excessive precipitation phase.
By synergistically adding Ti and Nb elements, the total content is controlled to be within the range of 0.05~0.35 wt.%, and high-temperature heat treatment is performed on the SC sheet containing Nb to promote the generation of the NbFeB phase, and mutual inhibition between the TiB2 phase and the NbFeB phase is achieved, forming fine and diffuse Ti3Nb and TiNb precipitates.
It effectively improves the strength and toughness of the magnet, improves the bending strength and angle resistance, reduces vibration weight loss, and enhances the impact energy absorption capacity of the magnet during collision.
Smart Images

Figure CN119811814A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a high-strength and high-toughness RTB rare earth permanent magnet and a preparation method thereof, belonging to the field of rare earth magnets. Background Art
[0002] As a functional material, the research on RTB rare earth permanent magnets has always focused on how to further improve their magnetic properties. In recent years, with the gradual expansion of the application field of RTB magnets, especially with the development of high-speed motors and their application in the field of electric vehicles, the requirements for their mechanical properties are getting higher and higher.
[0003] RTB rare earth permanent magnet is a brittle material, which is prone to brittle fracture when subjected to stress, which seriously restricts the use environment of the material. The main reasons for the poor mechanical properties of RTB rare earth permanent magnets are as follows: first, the main phase of the magnet is a complex intermetallic compound that cannot slip or twin deformation, so it is easy to brittle fracture when subjected to stress; second, the strength of the grain boundary R-rich phase is low and the ability to resist crack propagation is poor, so cracks are easy to propagate along the grain boundary R-rich phase; finally, RTB magnets have the characteristics of uneven microstructure, uneven grain size of the main phase and uneven distribution of the grain boundary R-rich phase, which easily lead to stress concentration.
[0004] Second phase strengthening is a common method to enhance the mechanical properties of RTB magnets. In current engineering practice, high melting point elements such as Zr, Ti and Nb are usually added to magnets and react with B to form borides, such as ZrB2, TiB2 and NbFeB. However, excessively large precipitates are prone to produce stray fields, resulting in reduced coercivity. At the same time, a single precipitate phase will continue to grow during long-term sintering, reducing dispersibility and hindering the enhancement of toughness. Summary of the invention
[0005] In view of the fact that the method of applying the precipitated phase in the traditional RTB magnet is relatively simple, the present invention provides a high-strength and high-toughness RTB rare earth permanent magnet and a preparation method thereof.
[0006] The technical solution adopted by the present invention is as follows: A high-strength, high-toughness RTB rare earth permanent magnet, the magnet composition comprises the following components in mass fraction: R: 28.5wt.%~34.0wt.%, R is one or more of Nd, Pr, Dy, Tb, Ho, Gd, La, Ce, Lu, Y, and at least contains one or more of the rare earth R1 elements, wherein the rare earth R1 element is Nd, Pr, Ce; B: 0.85~1.1wt.%, TN: 0.05~0.35wt.%, TN represents Ti and Nb elements, and the total mass content of Ti and Nb elements is 0.05~0.35wt.%; M: 0.01-8.0wt.%, M represents one or more of Al, Cu, Ga, Ni, Zn, Sn, and Mn; The balance is T and other unavoidable impurities, T is Fe or Fe and Co; And it satisfies: 1.5×[Nb] / 92.91≤[Ti] / 47.87≤2.5×[Nb] / 92.91, wherein [Ti] is the content of Ti expressed in mass fraction, and [Nb] is the content of Nb expressed in mass fraction.
[0007] The RTB rare earth permanent magnet contains both Ti3Nb precipitates and TiNb precipitates.
[0008] Furthermore, in the RTB rare earth permanent magnet, Ti3Nb precipitates and TiNb precipitates with a length greater than 10 nm exist in the triangular grain boundary phase region surrounded by the main phase grains.
[0009] The high-strength, high-toughness RTB rare earth permanent magnet can be prepared by the following method: (1) According to the magnet formula, SC sheets containing Ti and SC sheets containing Nb are prepared respectively, so that after the SC sheets containing Ti and SC sheets containing Nb are mixed according to the ratio, the magnet formula is satisfied, and the total mass content of Ti and Nb elements is 0.05-0.35wt.%, and the following is satisfied: 1.5×[Nb] / 92.91≤[Ti] / 47.87≤2.5×[Nb] / 92.91; The SC sheet containing Ti does not contain Nb element, and the SC sheet containing Nb does not contain Ti element; (2) The Nb-containing SC sheet is subjected to high temperature heat treatment, wherein the temperature of the high temperature heat treatment is 800-1050°C (preferably 900-1050°C); (3) The Ti-containing SC sheet and the Nb-containing SC sheet after high temperature heat treatment in step (2) are mixed according to a ratio, and the resulting mixed SC sheet is used to prepare an RTB rare earth permanent magnet according to a conventional process.
[0010] The present invention also provides a method for preparing the high-strength and high-toughness RTB rare earth permanent magnet, the method comprising: (1) According to the magnet formula, SC sheets containing Ti and SC sheets containing Nb are prepared respectively, so that after the SC sheets containing Ti and SC sheets containing Nb are mixed according to the ratio, the magnet formula is satisfied, and the total mass content of Ti and Nb elements is 0.05-0.35wt.%, and the following is satisfied: 1.5×[Nb] / 92.91≤[Ti] / 47.87≤2.5×[Nb] / 92.91; The SC sheet containing Ti does not contain Nb element, and the SC sheet containing Nb does not contain Ti element; (2) The Nb-containing SC sheet is subjected to high temperature heat treatment, wherein the temperature of the high temperature heat treatment is 800-1050°C (preferably 900-1050°C); (3) The Ti-containing SC sheet and the Nb-containing SC sheet after high temperature heat treatment in step (2) are mixed according to a ratio, and the resulting mixed SC sheet is used to prepare an RTB rare earth permanent magnet according to a conventional process.
[0011] Specifically, in step (3), the mixed SC sheets are subjected to hydrogen crushing and air flow grinding to obtain powder; the obtained powder is subjected to compression molding, isostatic pressing, and then vacuum sintering and aging treatment to obtain RTB rare earth permanent magnets.
[0012] In the step (2), the high temperature heat treatment time is 0.5 to 5 hours.
[0013] In the step (2), the high temperature heat treatment is performed in a vacuum environment or under argon protection.
[0014] Furthermore, in the step (2), the high temperature heat treatment process of the Nb-containing SC sheet is carried out according to the following steps: placing the Nb-containing SC sheet in a molybdenum boat, and then placing it in a heating furnace; heating to 900-1050° C. in a vacuum environment or under argon protection, and keeping the temperature for 0.5-5 hours; cooling to room temperature after the heat treatment is completed.
[0015] The argon pressure is generally 2~3kPa.
[0016] The vacuum sintering is generally carried out in a vacuum sintering furnace at a temperature of 1040-1150° C. for 3-15 hours (preferably 3-6 hours).
[0017] The aging treatment refers to a primary aging treatment process in which the sintered magnet is subjected to a temperature of 700-900°C for 2-8 hours, then cooled to below 100°C at a rate of not less than 20°C / min, and then heated to 400-600°C for a secondary aging treatment of 2-8 hours, and then cooled to below 80°C at a rate of not less than 30°C / min.
[0018] Second phase strengthening is a common method to enhance the mechanical properties of RTB magnets. In current engineering practice, high melting point elements such as Zr, Ti and Nb are usually added to magnets and react with B to form borides, such as ZrB2, TiB2 and NbFeB. However, too large precipitated phases are prone to generate stray fields, resulting in reduced coercivity. At the same time, a single precipitated phase will continue to grow during long-term sintering, reducing dispersibility and hindering the enhancement of toughness. The present invention regulates the composition of the magnet so that the magnet contains Ti and Nb, and the total content of the two ranges from 0.05 to 0.35wt.%, and at the same time, the content of Ti and Nb satisfies 1.5×[Nb] / 92.91≤[Ti] / 47.87≤2.5×[Nb] / 92.91, wherein [Ti] is the content of Ti expressed in mass fraction, and [Nb] is the content of Nb expressed in mass fraction. Combined with the pre-heat treatment of the Nb-containing SC sheet to promote the formation of the NbFeB phase, the mutual inhibition of the TiB2 phase and the NbFeB phase during the sintering process is achieved. At the same time, the Ti3Nb and TiNb precipitates grow competitively, achieving a finer and more dispersed precipitate phase, which can more effectively improve the magnet strength and toughness.
[0019] The present invention performs high-temperature heat treatment on the SC sheet containing Nb to promote the nucleation and initial growth of NbFeB in the SC sheet. Experiments show that NbFeB precipitates can be formed by heat treatment above 900°C. Too high a temperature will cause the main phase to grow and reduce the coercive force. The Ti-containing SC has formed a certain amount of TiB2 phase after melt spinning. The present invention performs heat treatment on the SC sheet containing Nb to promote the formation of NbFeB precipitates in order to ensure the competitive growth relationship of the two precipitate phases during the mixed powder making and sintering process, thereby inhibiting the excessive growth of a single precipitate phase. In order to ensure that the material does not oxidize during the heat treatment process, it is necessary to carry out the treatment in a vacuum or in argon protection.
[0020] After hydrogen breaking and jet milling, the SC sheets are homogenized along with the mixing process of magnetic powder.
[0021] The present invention adds a certain amount of Ti and Nb to the raw materials to melt different SC sheets, and adjusts the ratio of Ti and Nb by mixing different SC sheets, obtains alloy powder through hydrogen cracking treatment and airflow grinding, and the alloy powder is molded in an oriented magnetic field and isostatically pressed. The molded magnet is prepared through vacuum sintering and aging treatment. Since it is difficult to find the precipitated phase (too fine or absent) in the SC sheet containing Nb, the SC sheet containing Nb is subjected to high-temperature heat treatment, thereby promoting the mutual inhibition between different precipitated phases during the sintering process and reducing the precipitation of Nb in the main phase. During the sintering process, Ti3Nb and TiNb precipitates will compete for growth together and consume a certain amount of TiB2 phase and NbFeB phase, thereby ensuring that the precipitated phase is more fine and dispersed. The fine precipitated phase exists in the grain boundary phase, hindering the crack from extending along a straight line, increasing the crack area and the energy consumed, and improving the strength and toughness of the magnet. It is common knowledge in the industry to control the precipitation phase elements such as Ti / Nb within a certain range to ensure that the remanence and coercive force do not deteriorate, and will not be described further.
[0022] The beneficial effects of the present invention are: By synergistically adding two high melting point elements of Ti and Nb, a variety of precipitation phases are mixed and precipitated to coexist. According to the formation process of the precipitation phase, the SC alloy sheet containing Nb is preferably subjected to high temperature heat treatment to ensure a certain amount of basic precipitation phase. During the sintering process, a variety of precipitation phases compete with each other to inhibit growth, and fine Ti3Nb phases and TiNb phases are precipitated in the grain boundary phase. The Ti3Nb precipitate particles with fine size have better dispersibility, thereby inhibiting crack propagation, improving the strength, toughness and anti-corner performance of the magnet, thereby preparing a magnet with both high strength and high toughness. The present invention adopts the synergistic addition of Ti and Nb elements to effectively improve the coercive force of the magnet, and the synergistic addition of Ti and Nb elements to precipitate can effectively improve the strength and toughness of the magnet at the same time, and the bending strength of the obtained magnet is significantly improved, and the vibration weightlessness is significantly reduced, and the stronger the impact energy absorbed during the collision, the toughness of the magnet is significantly enhanced. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 The microstructure of the Ti-containing SC sheet without heat treatment and the microstructure of the Nb-containing SC sheet after high-temperature heat treatment.
[0024] Figure 2 This is a diagram of the crack diffusion of sintered magnets in Experiment No. 1~4.
[0025] Figure 3 This is the TEM microstructure and selected area electron diffraction pattern of the sintered magnet precipitate from Experiment No. 2.
[0026] Figure 4 This is the TEM microstructure and selected area electron diffraction pattern of the sintered magnet precipitate from Experiment No. 3.
[0027] Figure 5 This is the TEM microstructure and selected area electron diffraction pattern of the sintered magnet precipitate from Experiment No. 4. DETAILED DESCRIPTION
[0028] The technical solution of the present invention is further described below in conjunction with specific embodiments, but the protection scope of the present invention is not limited thereto.
[0029] The present invention adopts vacuum induction melting and belt throwing, takes raw materials with a purity of more than 99.9% according to the composition ratio, puts them into the crucible in order from high to low melting points, and evacuates the furnace until the vacuum degree reaches 10 -1 Pa, the dew point is lower than -50℃. Then fill the furnace with argon gas to make the pressure reach 30~50kPa, and heat it to 1480~1510℃. After the raw materials are completely melted, keep it warm for 3~5min. Then reduce the temperature of the alloy liquid to 1440~1460℃, and keep it warm and cast it. Adjust the speed of the copper roller to 70~75 rpm, and then rotate the crucible at a certain speed, so that the molten alloy liquid is transported to the cooling roller through the tundish for solidification and then falls on the water cooling plate to cool down, and the SC sheet is obtained.
[0030] The SC sheet prepared by smelting is subjected to high temperature heat treatment. The alloy sheet obtained by smelting is placed in a molybdenum boat, placed in a heating furnace, and heated to 900~1050℃ in a vacuum environment. After heat treatment for 1h, it is cooled to room temperature and cooled with the furnace.
[0031] Individual SC alloy flakes or alloy flakes mixed in a certain proportion are prepared into alloy powders by hydrogen crushing and air flow milling. During hydrogen crushing treatment, the hydrogen pressure in the reactor is generally 0.01~0.09MPa. During the hydrogen absorption reaction, the pressure change in the reactor does not exceed 0.5% within 10 minutes, which represents saturated hydrogen absorption. After the saturated hydrogen absorption reaction is completed, the temperature is raised to between 400~600℃ while evacuating the vacuum, and the temperature is kept for 2~6h to release the hydrogen in the alloy flakes, and then cooled to obtain hydrogen crushed coarse powder. The obtained coarse powder is placed in a jet mill, and in an inert gas atmosphere, the nozzle pressure is adjusted to between 0.6MPa~0.8MPa, and the coarse powder is driven by high-speed gas to collide with each other for crushing. The inert gas is generally nitrogen.
[0032] After subsequent jet milling, the precipitate is homogenized along with the mixing process of magnetic powder.
[0033] After adding lubricant and / or antioxidant to the alloy powder, the alloy powder is molded in an oriented magnetic field, and conventional commercially available magnetic powder protection lubricant or antioxidant can be used. The amount of lubricant added can be 0.01-0.1% of the mass of the alloy powder, and the amount of antioxidant added can be 0.01-0.14% of the mass of the alloy powder.
[0034] The orientation magnetic field is preferably 1.8-3T, and the molding pressure is 5-10MPa. After orientation molding, the green compact is subjected to cold isostatic pressing at a pressure of 150-180MPa. The density of the green compact after orientation molding is 3.6-4.0g / cm 3 The density of the green compact after cold isostatic pressing is about 4.6 g / cm 3 .
[0035] Whether to perform cold isostatic pressing after molding can be selected according to the process. The present invention selects to perform cold isostatic pressing on the green compact after orientation molding to further eliminate cracks inside the green compact.
[0036] The vacuum sintering process is used to sinter the magnets to a compact size. The sintering temperature can be gradually increased according to a certain heating curve, and the temperature can be kept at the highest temperature range of 1040~1150℃ for more than 3 hours.
[0037] The sintered magnet needs to undergo a two-stage aging process. First, the primary aging treatment process is carried out at 700~900℃ for 2~8h, then cooled to below 100℃ at a rate of not less than 20℃ / min, and then heated to 400~600℃ for 2~8h of secondary aging treatment. After the end, it is cooled to below 80℃ at a rate of not less than 30℃ / min.
[0038] The microstructure of SC alloy sheet and magnet was observed by SEM and TEM. The three-point bending sample was prepared by inner circle slicer and double-sided grinding. The sample size was 25 (±0.01) mm × 6 (±0.01) mm × 5 (±0.01 mm) in length × width × height. The height direction of the sample was parallel to the orientation direction of the magnet. The bending strength of the magnet was measured by three-point bending method according to GB / T31967.2-2015. Ten samples were measured in each group of experiments and the average value was calculated. The three-point bending indenter was a cylinder with a diameter of 5 mm, the diameter of the two support columns was 5 mm, the span between the fulcrums was 14.5 mm, and the pressing speed of the indenter was 0.1 mm / min. The magnetic properties measurement sample was prepared by wire cutting, double-sided grinding and end grinding. The sample was a φ10 mm × 10 mm cylinder, and the magnetic properties of the magnet were measured by NIM equipment. The magnet toughness was characterized by the vibration weightlessness method provided in patent document CN116223262A. The sample size was 15 (±0.01) mm × 15 (±0.01) mm × 5 (±0.01 mm) in length × width × height, and the sample height direction was parallel to the magnet orientation direction. After the magnet was polished, the magnet hardness was tested with a Vickers hardness tester. The test surface was perpendicular to the magnet orientation direction. Each sample was tested for 10 values and the average value was taken as its hardness value.
[0039] Embodiment 1: Add materials according to the formula in Table 1. For low melting point metals, pure metals with a purity of more than 99.9wt.% are used as raw materials. For elements with a melting point higher than pure iron, alloys of the element and iron are used as raw materials. Put them into the crucible in descending order of melting point, and evacuate the furnace until the vacuum reaches 10 -2 Pa, the dew point is lower than -50℃. Then fill the furnace with argon gas to make the gas pressure reach 30kPa, and heat it to 1490℃. After the raw materials are completely melted, keep it warm for 3 minutes. Then reduce the temperature of the alloy liquid to 1450℃ and cast it. Adjust the speed of the copper roller to 70 rpm, and then rotate the crucible at a certain speed, so that the molten alloy liquid is transported to the cooling roller through the tundish for solidification and then falls on the water cooling plate to cool down, and obtain an alloy sheet with a thickness of 0.28±0.05mm.
[0040] The SC sheet containing Nb prepared by smelting is subjected to high temperature heat treatment. The alloy sheet obtained by smelting is placed in a molybdenum boat and placed in a heating furnace. The vacuum degree in the furnace is drawn to 10 -3 Pa and heated to 1000℃, kept warm for 60min, and cooled to room temperature with the furnace after the heat treatment.
[0041] As attached Figure 1 The microstructure of the precipitation phase of the Ti-containing flakes without heat treatment and the microstructure of the precipitation phase of the Nb-containing flakes after heat treatment (no precipitation phase was found in the microstructure of the Nb-containing flakes without heat treatment). It can be found that the TiB2 phase precipitates in the Ti-containing flakes without heat treatment, but the NbFeB precipitation phase is not found in the Nb-containing flakes without heat treatment, while the NbFeB precipitation phase is easily found in the flakes after high-temperature heat treatment. This shows that the nucleation difficulty and growth rate of different precipitation phases are different. Different heat treatments are selected for SC flakes containing different elements, and the relative size and content of different precipitation phases in the mixed flakes can be adjusted.
[0042] The alloy flakes were subjected to saturated hydrogen absorption reaction under a hydrogen pressure of 0.09MPa. After the hydrogen absorption reaction, the temperature was raised to 550°C while evacuating the air, and the temperature was kept for 4 hours to release the hydrogen in the alloy flakes, and then cooled to obtain hydrogen-crushed coarse powder. After cooling, 0.05wt.% zinc stearate was added to the coarse powder and mixed for 3 hours. The coarse powder was further crushed by a nitrogen gas flow mill to obtain fine powder, and the gas pressure was 0.6MPa. Among them, Experiment 4 was to mix the SC flakes of Experiment 2 and Experiment 3 in a certain proportion and then perform hydrogen crushing and powder making.
[0043] Add 0.03wt.% of organic lubricant (magnetic powder protection lubricant 3# produced by Tianjin Yuesheng New Materials Research Institute) to the fine powder and mix for 3 hours. The fine powder after mixing is oriented and formed under a magnetic field. The orientation magnetic field is a static magnetic field of 2.5T and the pressing pressure is 5MPa. The density of the magnet after pressing is 3.9~4.0g / cm 3After that, cold isostatic pressing is performed with a pressing pressure of 160MPa. The density of the magnet after pressing is greater than 4.6g / cm 3 .
[0044] The magnet is sintered to a compact size using a vacuum sintering process. The vacuum sintering process has a vacuum degree of 10 -3 Below Pa, the temperature is raised to 1080℃ in stages for high temperature sintering, and the holding time is 3h.
[0045] The sintered magnet needs to undergo a two-stage aging process. First, the primary aging treatment process is carried out at 880℃ for 3h, then cooled to below 100℃ at a rate of not less than 20℃ / min, and then heated to 500℃ for 3h of secondary aging treatment. After the end, it is cooled to below 80℃ at a rate of not less than 30℃ / min.
[0046] The SC alloy sheet and magnet microstructure were observed by SEM and TEM, and the magnet micro-region composition and structure were analyzed by TEM. The bending strength of the magnet was measured by the three-point bending method according to GB / T31967.2-2015. Ten samples were measured in each group of experiments and the average value was calculated. The magnetic properties of the magnet were measured by NIM equipment, and the toughness of the magnet was characterized by the vibration weightlessness method provided in patent document CN116223262A. The hardness of the magnet was tested by Vickers hardness tester.
[0047] The magnet components of each experimental group are expressed in mass fraction, as shown in Table 1: Table 1 No. Nd Pr Dy B Co Cu Ga Al Ti Nb Fe Mixing 1 22.3 7.7 0.2 0.96 0.5 0.15 0.12 0.2 0 0 Bal single 2 22.3 7.7 0.2 0.96 0.5 0.15 0.12 0.2 0.35 0 Bal single 3 22.3 7.7 0.2 0.96 0.5 0.15 0.12 0.2 0 0.35 Bal single 4 22.3 7.7 0.2 0.96 0.5 0.15 0.12 0.2 0.175 0.175 Bal 2+3 mass ratio 1:1 The magnet properties of each experimental group are shown in Table 2: Table 2 No. Br HkDJ Hk / Hcj 1 13.91 14.17 90.1% 2 14.00 14.65 97.3% 3 14.06 14.96 98.0% 4 13.99 15.18 99.0% Experiment No. 1 does not add Ti and Nb, Experiment No. 2 and Experiment No. 3 magnets add Ti and Nb respectively, and Experiment No. 4 magnets have Ti and Nb elements in a weight ratio of 1:1. From the data in Tables 1 and 2, it can be seen that the remanence of Experiment No. 3 magnets is slightly higher than Experiment No. 1 and Experiment No. 2, while the coercive force of Experiment No. 3 magnets is significantly higher than Experiment No. 1 and Experiment No. 2, indicating that the synergistic addition of Ti and Nb elements can effectively improve the coercive force of the magnet.
[0048] The bending strength, Vickers hardness and vibration weight loss of the magnets in each experimental group are shown in Table 3: Table 3 No. Flexural strength (MPa) Vibration weight loss (%) Hardness (Hv) 1 293.9 0.12 583 2 239.3 0.35 607 3 293.3 0.26 592 4 332.5 0.08 567 It can be seen that the bending strength of Experiment No.2 and Experiment No.3 is inferior to that of Experiment No.1, while the bending strength of Experiment No.4 magnet is significantly higher than that of Experiment No.2 and Experiment No.3 and Experiment No.1, indicating that excessive Ti or Nb is added alone, the precipitation phase is too large, and the difference in mechanical properties of different phases is easy to cause stress concentration, which reduces the strength of the magnet. The method of using Ti and Nb elements to add mixed precipitation can effectively improve the strength of the magnet. It can be seen from the magnet hardness and vibration weight loss data that the hardness and vibration weight loss of Experiment No.4 magnet are lower than those of Experiment No.1~3. The smaller the vibration weight loss of the magnet, the stronger the magnet absorbs impact energy during the collision, that is, the higher the toughness of the magnet, and the reduction in hardness also represents the improvement of the toughness of the magnet. The present invention uses Ti and Nb elements to add and precipitate together to improve the strength and toughness of the magnet at the same time.
[0049] Figure 2 Figures (1) to (4) show the crack extension of the sintered magnets in Experiment No. 1 to Experiment No. 4, respectively. The cracks of the magnets in Experiment No. 1 without adding Ti / Nb elements are wide and spread along the grain boundaries; the cracks of the magnets in Experiment No. 2 and Experiment No. 3 with added Ti or Nb elements are along the grain boundaries and the interface of the bulk precipitated phase; while the cracks of the magnets in Experiment No. 4 with mixed precipitation of Ti and Nb are difficult to penetrate the grain boundary phase region where the precipitated phase is located. It can be inferred that the fine dispersion of the mixed precipitate phase effectively inhibits crack extension and can improve the toughness of the magnet.
[0050] Figure 3-5 The TEM microstructures and selected area electron diffraction patterns of the precipitates of the sintered magnets of Experiment No. 2 to Experiment No. 4 are respectively. In Experiment No. 2, only Ti element was added to the magnet, and the precipitates in the sintered magnet were rod-shaped. The selected area electron diffraction results showed that the precipitates were TiB2. In Experiment No. 3, only Nb element was added to the magnet, and the precipitates were mainly blocky. The selected area electron diffraction results showed that the precipitates were NbFeB. In Experiment No. 4, Ti and Nb elements were added synergistically. From the TEM microstructure, it can be seen that there are at least two precipitates Ti3Nb and TiNb in the sintered magnet, and the length of the TiNb precipitate phase is greater than 10nm. However, the size is smaller than that of the precipitates in Experiment No. 2 and Experiment No. 3. The competitive growth between the mixed precipitates promotes the precipitates to be finer and more dispersed, increases the strength of the grain boundary phase, and thus achieves both magnet strengthening and toughening. The stray field generated by the fine precipitates is smaller, which can improve the coercive force to a certain extent.
[0051] Embodiment 2: Add materials according to the formula in Table 4. For low melting point metals, pure metals with a purity of more than 99.9wt.% are used as raw materials (PrNd alloy is the industry's conventional 25wt.% Pr). For elements with a melting point higher than pure iron, alloys of the element and iron are used as raw materials. Put them into the crucible in descending order of melting point, and evacuate the furnace until the vacuum reaches 10 -1 Pa, the dew point is lower than -50℃. Then fill the furnace with argon gas to make the gas pressure reach 30kPa, and heat it to 1490℃. After the raw materials are completely melted, keep it warm for 3 minutes. Then reduce the temperature of the alloy liquid to 1450℃ and cast it. Adjust the speed of the copper roller to 70 rpm, and then rotate the crucible at a certain speed, so that the molten alloy liquid is transported to the cooling roller through the tundish for solidification and then falls on the water cooling plate to cool down, and obtain an alloy sheet with a thickness of 0.28±0.05mm.
[0052] The Nb-containing SC sheet prepared by smelting was subjected to high-temperature heat treatment at a temperature of 900° C. for 2 hours, and then cooled to room temperature along with the furnace after the heat treatment was completed.
[0053] A single alloy sheet or a mixed alloy sheet mixed according to Table 4 is saturated with hydrogen in a hydrogen crushing furnace reactor. After the hydrogen absorption reaction is completed, the temperature is raised to 550°C while evacuating the vacuum, and the temperature is kept for 4 hours to release the hydrogen in the alloy sheet, and then cooled to obtain a hydrogen crushed coarse powder. After cooling, 0.05wt.% zinc stearate is added to the coarse powder and mixed for 3 hours. The coarse powder is further crushed by a nitrogen gas jet mill to obtain a fine powder, and the gas pressure is 0.6MPa.
[0054] Add 0.03wt.% of organic lubricant (magnetic powder protection lubricant 3# produced by Tianjin Yuesheng New Materials Research Institute) to the fine powder and mix for 3 hours. The fine powder after mixing is oriented and formed under a magnetic field. The orientation magnetic field is a static magnetic field of 2.5T and the pressing pressure is 5MPa. The density of the magnet after pressing is 3.9~4.0g / cm 3 After that, cold isostatic pressing is performed with a pressing pressure of 160MPa. The density of the magnet after pressing is greater than 4.6g / cm 3 .
[0055] The magnet is sintered to a compact size using a vacuum sintering process. The vacuum sintering process has a vacuum degree of 10 -3 Pa, and then heat up in stages to 1050-1095℃ after the insulation is completed, and sintering is carried out in the high temperature stage, and the insulation time is 8h.
[0056] The sintered magnet needs to undergo a two-stage aging process. First, the primary aging treatment process is carried out at 880℃ for 3h, then cooled to below 100℃ at a rate of not less than 20℃ / min, and then heated to 500℃ for 3h of secondary aging treatment. After the end, it is cooled to below 80℃ at a rate of not less than 30℃ / min.
[0057] After the magnet is broken, a sample is taken from the center and the magnet composition is detected by ICP. The magnet microstructure is analyzed by SEM and the 1mm 2 The proportion of high melting point element borides to high melting point element precipitates within the range. The bending strength of the magnet is measured by the three-point bending method in accordance with GB / T31967.2-2015. Ten samples are measured in each group of experiments and the average value is calculated. The magnetic properties of the magnet are measured using NIM equipment, and the toughness of the magnet is characterized according to the vibration weightlessness method provided in patent document CN116223262A. The hardness of the magnet is tested using a Vickers hardness tester.
[0058] The magnet components of each experimental group are expressed in mass fraction, as shown in Table 4: Table 4 No. PcqI Tb B Co Cu Ga Ti Nb Fe Mixing Proportion 4 30.25 0.3 0.95 0.5 0.2 0.3 0.04 0 Bal single / 5 30.25 0.3 0.95 0.5 0.2 0.3 0.4 0 Bal single / 6 30.25 0.3 0.95 0.5 0.2 0.3 0 0.06 Bal single / 7 30.25 0.3 0.95 0.5 0.2 0.3 0 0.3 Bal single / 8 30.25 0.3 0.95 0.5 0.2 0.3 0.024 0.024 Bal 4+6 6:4 9 30.25 0.3 0.95 0.5 0.2 0.3 0.02 0.03 Bal 4+6 5:5 10 30.25 0.3 0.95 0.5 0.2 0.3 0.24 0.12 Bal 5+7 6:4 11 30.25 0.3 0.95 0.5 0.2 0.3 0.16 0.18 Bal 5+7 4:6 The magnet properties of each experimental group are shown in Table 5: Table 5 No. Br HkDJ Hk / Hcj 4 14.19 16.1 91.1% 5 13.83 17.2 97.6% 6 14.20 16.3 89.7% 7 13.94 17.7 98.6% 8 13.92 16.9 93.1% 9 13.96 17.4 95.2% 10 13.89 17.9 97.3% 11 13.95 18.8 99.2% The bending strength, Vickers hardness and vibration weight loss of the magnets in each experimental group are shown in Table 6: Table 6 No. Flexural strength (MPa) Vibration weight loss (%) Hardness (Hv) 4 301.3 0.37 627.1 5 256.2 0.35 640.6 6 303.5 0.23 584.3 7 271.0 0.22 574.2 8 302.2 0.15 579.5 9 337.3 0.08 554.1 10 301.5 0.17 615.3 11 341.2 0.05 544.8 In this embodiment, the total content and ratio of Ti and Nb elements in the magnets of Experiment No. 9 and Experiment No. 11 meet the requirements of the present invention, so the magnets have high strength and toughness. The Ti content of the magnet of Experiment No. 4 is too little, resulting in insufficient number of precipitated phases, and the effect of second phase precipitation strengthening cannot be exerted. The Ti content of the magnet of Experiment No. 5 is too much, which is easy to form a larger precipitated phase, resulting in uneven local stress concentration, which will lead to a decrease in magnet strength and an increase in hardness. The total content of Nb elements in the magnets of Experiment No. 6 and No. 7 is within the required range of the present invention, but the content of Ti and Nb does not meet the ratio requirement of 1.5×[Nb] / 92.91≤[Ti] / 47.87≤2.5×[Nb] / 92.91 (only Nb element is added). The single precipitated phase content is too little (No. 6) or lacks a competitive relationship and grows too large (No. 7), which is not conducive to the improvement of mechanical properties. Although the Ti and Nb contents of the experimental No. 8 magnet meet the ratio requirement of 1.5×[Nb] / 92.91≤[Ti] / 47.87≤2.5×[Nb] / 92.91, too little total content of Ti and Nb elements will only form too few Ti3Nb and TiNb precipitation phases, and cannot fully achieve the strengthening effect of grain boundary precipitation phase. In No. 10, the total content of Ni and Nb exceeds 0.35%, and there are too many precipitation phases, which can easily lead to a large difference in hardness between the main phase and the grain boundary phase, resulting in internal stress, which is not conducive to improving the mechanical properties of the magnet; at the same time, the volume proportion of the non-magnetic phase increases, and the remanence of the magnet will gradually decrease.
[0059] Embodiment three: Add materials according to the formula in Table 7. For low melting point metals, pure metals with a purity of more than 99.9wt.% are used as raw materials (PrNd alloy is the industry's conventional 25wt.% Pr). For elements with a melting point higher than pure iron, alloys of the element and iron are used as raw materials. Put them into the crucible in descending order of melting point, and evacuate the furnace until the vacuum reaches 10 -1 Pa, dew point is lower than -50℃. Then fill the furnace with argon gas to make the pressure reach 30kPa, and heat it to 1500℃. After the raw materials are completely melted, keep it warm for 3 minutes. Then reduce the temperature of the alloy liquid to 1420℃ and cast it. Adjust the speed of the copper roller to 70 rpm, and then rotate the crucible at a certain speed, so that the molten alloy liquid is transported to the cooling roller through the tundish for solidification and then falls on the water cooling plate to cool down, and obtain an alloy sheet with a thickness of 0.30±0.05mm.
[0060] The SC sheet containing Nb prepared by smelting is subjected to high temperature heat treatment. The alloy sheet containing Nb prepared by smelting is placed in a molybdenum boat and placed in a heating furnace. The vacuum degree in the furnace is drawn to 10 -3 Pa and heated to 1050℃, when the temperature reached the target temperature, kept warm for 30 minutes, and cooled to room temperature with the furnace after the heat treatment was completed.
[0061] A single alloy sheet or alloy sheets mixed according to the ratio in Table 7 were subjected to saturated hydrogen absorption under a hydrogen pressure of 0.09 MPa. After the hydrogen absorption reaction was completed, the temperature was raised to 500°C while evacuating the vacuum, and the temperature was kept for 4 hours to release the hydrogen in the alloy sheet, and then cooled to obtain hydrogen-crushed coarse powder. After cooling, 0.05wt.% zinc stearate was added to the coarse powder and mixed for 3 hours, and the coarse powder was further crushed by a nitrogen gas jet mill to obtain fine powder, and the gas pressure was 0.6MPa.
[0062] Add 0.03wt.% of organic lubricant (magnetic powder protection lubricant 3# produced by Tianjin Yuesheng New Materials Research Institute) to the fine powder and mix for 3 hours. The fine powder after mixing is oriented and formed under a magnetic field. The orientation magnetic field is a static magnetic field of 2.5T and the pressing pressure is 5MPa. The density of the magnet after pressing is 3.9~4.0g / cm 3 After that, cold isostatic pressing is performed with a pressing pressure of 160MPa. The density of the magnet after pressing is greater than 4.6g / cm 3 .
[0063] The magnets are sintered densely by vacuum sintering process. The temperature is raised in stages, and the temperature is lowered after being kept at 1075℃ for 6 hours. The sintered magnets need to undergo a two-stage aging process. First, the primary aging process is carried out at 900℃ for 3 hours, then cooled to below 100℃ at a rate of not less than 20℃ / min, and then heated to 500℃ for 3 hours of secondary aging treatment. After the end, it is cooled to below 80℃ at a rate of not less than 30℃ / min.
[0064] After the magnet is crushed, a sample is taken from the center, the magnet composition is detected by ICP, and the magnet microstructure is observed by SEM. The bending strength of the magnet is measured by the three-point bending method in accordance with GB / T31967.2-2015. Ten samples are measured in each group of experiments and the average value is calculated. The magnetic properties of the magnet are measured by NIM equipment, and the toughness of the magnet is characterized by the vibration weightlessness method provided in patent document CN116223262A. The hardness of the magnet is tested by a Vickers hardness tester.
[0065] Table 7 No. PcqI G B Co Cu Ga Ti Nb Fe Mixing Proportion 12 30.25 0.3 0.95 0.5 0.1 0.15 0.2 0 Bal single / 13 30.25 0.3 0.95 0.5 0.1 0.15 0 0.2 Bal single / 14 30.25 0.3 0.95 0.5 0.1 0.15 0.0872 0.1128 Bal 12+13 43.6:56.4 15 30.25 0.3 0.95 0.5 0.1 0.15 0.1 0.1 Bal 12+13 50:50 16 30.25 0.3 0.95 0.5 0.1 0.15 0.1126 0.0874 Bal 12+13 56.3:43.7 The magnet properties of each experimental group are shown in Table 8: Table 8 No. Br HkDJ Hk / Hcj 12 14.10 14.0 98.1% 13 14.15 13.8 98.6% 14 14.14 14.7 98.6% 15 14.14 14.6 98.5% 16 14.17 14.2 98.3% The bending strength, Vickers hardness and vibration weight loss of the magnets in each experimental group are shown in Table 11: Table 9 No. Flexural strength (MPa) Vibration weight loss (%) Hardness (Hv) 12 297.5 0.22 624.1 13 301.3 0.19 615.3 14 351.7 0.05 534.8 15 386.1 0.03 539.6 16 369.6 0.04 532.9 According to Table 7, the addition ratio of Ti and Nb elements is optimized. Since the total amount of Ti and Nb elements is within the commonly used optimal range, there is no significant difference in magnetic properties, except that the coercive force of Experiment No. 14-16 is slightly increased. Experiment No. 12 and No. 13 magnets are single elements that produce a single precipitate phase. The precipitate phase is easy to grow and has no good dispersion effect, resulting in relatively low mechanical properties. In Experiments NO. 14~16, the total content of Ti and Nb meets the requirements of the present invention and meets 1.5×[Nb] / 92.91≤[Ti] / 47.87≤2.5×[Nb] / 92.91, and the strength and toughness are significantly improved.
[0066] The present invention limits the ratio of Nb and Ti elements within a certain range, which will form dispersed and fine precipitated phases of Ti3Nb and TiNb. Due to the competitive relationship, the growth of TiB2 and NbFeB precipitated phases is also restricted. The mixed precipitation of multiple precipitated phases improves the uniformity of strengthening, thereby improving the bending strength and toughness of the magnet.
[0067] Embodiment 4: For low melting point metals, pure metals with a purity of more than 99.9wt.% are used as raw materials (PrNd alloy is the industry's conventional 25wt.%Pr). For elements with a melting point higher than pure iron, alloys of the element and iron are used as raw materials. Put them into the crucible in order from high to low melting points. The formula is shown in Table 10. Evacuate the furnace until the vacuum reaches 10 -1 Pa, dew point is lower than -50℃. Then fill the furnace with argon gas to make the pressure reach 30kPa, and heat it to 1490℃. After the raw materials are completely melted, keep it warm for 3 minutes. Then reduce the temperature of the alloy liquid to 1415℃ and cast it. Adjust the speed of the copper roller to 70 rpm, and then rotate the crucible at a certain speed, so that the molten alloy liquid is transported to the cooling roller through the tundish for solidification and then falls on the water cooling plate to cool down, and obtain an alloy sheet with a thickness of 0.30±0.05mm.
[0068] The SC sheet containing Nb prepared by smelting was divided into two parts, one part was subjected to high temperature heat treatment, and the other part was not subjected to high temperature treatment, as shown in Table 10. The alloy sheet containing Nb prepared by smelting was placed in a molybdenum boat and placed in a heating furnace. The vacuum degree in the furnace was drawn to 10 -3 Pa and heated to 980℃, when the temperature reached the target temperature, kept warm for 80 minutes, and cooled to room temperature with the furnace after the heat treatment was completed.
[0069] The alloy flakes mixed in a certain proportion are subjected to saturated hydrogen absorption under a hydrogen pressure of 0.09MPa. After the hydrogen absorption reaction is completed, the temperature is raised to 500°C while vacuuming, and the temperature is kept for 4 hours to release the hydrogen in the alloy flakes, and then cooled to obtain hydrogen-crushed coarse powder. After cooling, 0.05wt.% zinc stearate is added to the coarse powder and mixed for 3 hours. The coarse powder is further crushed to obtain fine powder using a nitrogen gas flow mill, and the gas pressure is 0.6MPa.
[0070] Add 0.03wt.% of organic lubricant (magnetic powder protection lubricant 3# produced by Tianjin Yuesheng New Materials Research Institute) to the fine powder and mix for 3 hours. The fine powder after mixing is oriented and formed under a magnetic field. The orientation magnetic field is a static magnetic field of 2.5T and the pressing pressure is 5MPa. The density of the magnet after pressing is 3.9~4.0g / cm 3 After that, cold isostatic pressing is performed with a pressing pressure of 160MPa. The density of the magnet after pressing is greater than 4.6g / cm 3 .
[0071] The vacuum sintering process is used to sinter the magnets to a compact size. The temperature is raised in stages, and the temperature is lowered after being kept at 1075℃ for 6 hours. The sintered magnets need to undergo a two-stage aging process. First, the primary aging process is carried out at 910℃ for 3 hours, then cooled to below 100℃ at a rate of not less than 20℃ / min, and then heated to 500℃ for 3 hours of secondary aging treatment. After the treatment, it is cooled to below 80℃ at a rate of not less than 30℃ / min.
[0072] After the magnet is crushed, a sample is taken from the center, the magnet composition is detected by ICP, and the magnet microstructure is observed by SEM. The bending strength of the magnet is measured by the three-point bending method in accordance with GB / T31967.2-2015. Ten samples are measured in each group of experiments and the average value is calculated. The magnetic properties of the magnet are measured by NIM equipment, and the toughness of the magnet is characterized by the vibration weightlessness method provided in patent document CN116223262A. The hardness of the magnet is tested by a Vickers hardness tester.
[0073] Table 10 No. PcqI Ho B Co Cu Ga Ti Nb Fe Mixing Proportion 17 30.2 1 0.95 0.5 0.1 0.15 0.2 0 Bal Not heat treated 18 30.2 1 0.95 0.5 0.1 0.15 0 0.2 Bal Not heat treated 19 30.2 1 0.95 0.5 0.1 0.15 0 0.2 Bal Heat Treatment 20 30.2 1 0.95 0.5 0.1 0.15 0.1 0.1 Bal 17+18 1:1 21 30.2 1 0.95 0.5 0.1 0.15 0.1 0.1 Bal 17+19 1:1 The magnet properties of each experimental group are shown in Table 8: Table 11 No. Br HkDJ Hk / Hcj 17 13.92 15.1 98.5% 18 14.01 15.2 98.7% 19 13.95 14.9 98.6% 20 13.97 15.2 98.6% 21 13.96 15.5 98.8% The bending strength, Vickers hardness and vibration weight loss of the magnets in each experimental group are shown in Table 11: Table 12 No. Flexural strength (MPa) Vibration weight loss (%) Hardness (Hv) 17 297.1 0.23 621.1 18 289.3 0.26 623.4 19 301.7 0.19 599.8 20 307.3 0.14 572.8 21 329.6 0.03 541.3 According to Table 10, it was explored whether the Nb-containing SC alloy sheet should be heat treated. Since the total amount of Ti and Nb elements are within the commonly used optimal range, there is no obvious difference in the magnetic properties. The magnets of Experiments No. 17-19 are all single elements that produce a single precipitate phase. The precipitate phase is easy to grow and there is no good dispersion effect, resulting in relatively low mechanical properties. It is worth noting that after the heat treatment of the Nb-containing SC alloy sheet in Experiment No. 19, the mechanical properties of the magnet will increase. This is because compared with the sintering temperature, the heat treatment temperature of the SC alloy sheet is lower, which is conducive to the precipitation of more NbFeB phases and avoids the rapid growth of a few NbFeB phases during high-temperature sintering. To a certain extent, the uniformity of the NbFeB phase precipitation phase is improved, and the mechanical properties are improved. Experiment No. 20 Since TiB2 is easier to precipitate than NbFeB phase (TiB is easily found in the unheat-treated Ti-containing SC alloy sheet 2, However, NbFeB phase was not found in the unheat-treated Nb-containing SC alloy sheet, and the competitive growth relationship was not effectively exerted during the mixed powder sintering process, resulting in low strength of the magnet. In experiment No. 21, after the Nb-containing SC alloy sheet was heat-treated, the NbFeB phase precipitated and grew. During the mixed powder sintering process, the two phases competed on the B element, and their growth was inhibited, which also created conditions for the precipitation of Ti3Nb and TiNb phases. The mixed precipitation of multiple precipitates improves the uniformity of strengthening, thereby improving the bending strength and toughness of the magnet.
Claims
1. A high-strength, high-toughness RTB rare earth permanent magnet, characterized in that The magnet composition comprises the following components by mass fraction: R: 28.5wt.%~34.0wt.%, R is one or more of Nd, Pr, Dy, Tb, Ho, Gd, La, Ce, Lu, Y, and at least contains one or more of the rare earth R1 elements, wherein the rare earth R1 element is Nd, Pr or Ce; B: 0.85~1.1wt.%, TN: 0.05~0.35wt.%, TN represents Ti and Nb elements, and the total mass content of Ti and Nb elements is 0.05~0.35wt.%; M: 0.01-8.0wt.%, M represents one or more of Al, Cu, Ga, Ni, Zn, Sn, and Mn; The balance is T and other unavoidable impurities, T is Fe or Fe and Co; And satisfy: 1.5×[Nb] / 92.91≤[Ti] / 47.87≤2.5×[Nb] / 92.91, wherein [Ti] is the content of Ti expressed in mass fraction, and [Nb] is the content of Nb expressed in mass fraction; The RTB rare earth permanent magnet contains both Ti3Nb precipitates and TiNb precipitates.
2. The high-strength, high-toughness RTB rare earth permanent magnet according to claim 1, characterized in that In the RTB rare earth permanent magnet, Ti3Nb precipitates and TiNb precipitates with a length greater than 10 nm exist in the triangular grain boundary phase region surrounded by the main phase grains.
3. The high-strength, high-toughness RTB rare earth permanent magnet according to claim 1 or 2, characterized in that The high-strength, high-toughness RTB rare earth permanent magnet is prepared by the following method: (1) According to the magnet formula, SC sheets containing Ti and SC sheets containing Nb are prepared respectively, so that after the SC sheets containing Ti and SC sheets containing Nb are mixed according to the ratio, the magnet formula is satisfied, and the total mass content of Ti and Nb elements is 0.05-0.35wt.%, and the following is satisfied: 1.5×[Nb] / 92.91≤[Ti] / 47.87≤2.5×[Nb] / 92.91; The SC sheet containing Nb does not contain Ti element; (2) The Nb-containing SC sheet is subjected to high temperature heat treatment, wherein the temperature of the high temperature heat treatment is 800-1050°C; (3) The Ti-containing SC sheet and the Nb-containing SC sheet after high temperature heat treatment in step (2) are mixed according to a ratio, and the resulting mixed SC sheet is used to prepare an RTB rare earth permanent magnet according to a conventional process.
4. The method for preparing the high-strength, high-toughness RTB rare earth permanent magnet according to claim 1 or 2, characterized in that The method is: (1) According to the magnet formula, SC sheets containing Ti and SC sheets containing Nb are prepared respectively, so that after the SC sheets containing Ti and SC sheets containing Nb are mixed according to the ratio, the magnet formula is satisfied, and the total mass content of Ti and Nb elements is 0.05-0.35wt.%, and the following is satisfied: 1.5×[Nb] / 92.91≤[Ti] / 47.87≤2.5×[Nb] / 92.91; The SC sheet containing Ti does not contain Nb element, and the SC sheet containing Nb does not contain Ti element; (2) The Nb-containing SC sheet is subjected to high temperature heat treatment, wherein the temperature of the high temperature heat treatment is 800-1050°C; (3) The Ti-containing SC sheet and the Nb-containing SC sheet after high temperature heat treatment in step (2) are mixed according to a ratio, and the resulting mixed SC sheet is used to prepare an RTB rare earth permanent magnet according to a conventional process.
5. The method according to claim 4, characterized in that In the step (2), the high temperature heat treatment is performed for 0.5 to 5 hours in a vacuum environment or under argon protection.
6. The method according to claim 4, characterized in that In the step (2), the high temperature heat treatment process of the Nb-containing SC sheet is carried out according to the following steps: placing the Nb-containing SC sheet in a molybdenum boat, and then placing it in a heating furnace; heating it to 900-1050° C. in a vacuum environment or under argon protection, and keeping it warm for 0.5-5 hours; cooling it to room temperature after the heat treatment is completed.
7. The method according to claim 4, characterized in that In the step (3), the mixed SC sheets are subjected to hydrogen crushing and air flow grinding to obtain powder; the obtained powder is subjected to compression molding, isostatic pressing, and then vacuum sintering and aging treatment to obtain RTB rare earth permanent magnets.
8. The method according to claim 7, characterized in that The vacuum sintering is carried out in a vacuum sintering furnace at a temperature of 1040-1150° C. for 3-15 hours.
9. The method according to claim 7, characterized in that The aging treatment refers to a primary aging treatment process in which the sintered magnet is subjected to a temperature of 700-900°C for 2-8 hours, then cooled to below 100°C at a rate of not less than 20°C / min, and then heated to 400-600°C for a secondary aging treatment of 2-8 hours, and then cooled to below 80°C at a rate of not less than 30°C / min.
Citation Information
Patent Citations
Method for evaluating brittleness of R-T-B rare earth permanent magnet
CN116223262A